Examining performance related determinants among UTAR Kampar undergraduates in adapting fifth industrial revolution (IR 5.0) technologies - Tham, Shi Yun (2024)
The Fifth Industry Revolution (IR 5.0) embarks on initiatives to solve environmental, social, and economic sustainability related problems. It emphasizes a synergistic partnership between human and smart machines that elevates productivity and ignites innovation at workplace. As IR 5.0 is reaching us soon, this study aims to identify the significant technological and self performance-related determinants among tertiary learners to adapt IR 5.0 technologies in their future workplaces. Technological performance-related determinants involve tertiary learners’ self-efficacy, perceived ease of use, perceived importance, behavioural intention to use, technological knowledge base and job performance expectancy on IR 5.0 technologies. Self performance-related determinants include tertiary learners’ life-long learning tendency, critical thinking, communication, collaboration, creativity, and problem-solving skills. Besides, this study examines inter-relationships among these determinants to provide valuable insights into the multifaceted dynamics that shape tertiary learners' proficiency and uptake of IR 5.0 technologies. In pursuit of these research goals, quantitative research via questionnaire survey was deployed. The study targets second-year and above undergraduates at Universiti Tunku Abdul Rahman (UTAR) Kampar by using multi-stage cluster sampling to select respondents from five faculties. A multi-staged cluster sampling technique was employed to select respondents from the five faculties. The questionnaire used in the study was compiled and adapted from recent literature sources. A total of 187 responses collected were analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). From the technological performance-related determinants analyzed, tertiary learners' self-efficacy, behavioural intention to use and technological knowledge base have significant influence on their readiness to adapt IR 5.0 technologies in their future workplaces. Furthermore, the relationship between perceived ease of use and behavioural intention to use IR 5.0 technologies is partially mediated by their perceived importance of these technologies. Based on tertiary learners’ self performance-related determinants studied, tertiary learners’ creativity skills significantly influence their readiness to adapt IR 5.0 technologies.